Restricciones del conocimiento científico - Lucas cabello, Adalberto (2017)
A look at the history of science or, more simply, to the evolution of societies where science has been institutionalized, can convince us that science has no limits in its ability to knowledge of the world, technological implementation and intervention in the course of physical events and social. However, this assumption should be regarded with caution and analyzed taking into account many elements. That is why we proposed demonstrate, by making use of the hermeneutical method, that scientific knowledge has its limits. After a rigorous work our students arrived to the conclusion that scientific knowledge if you have limits. Among the elements that were considered as possible limits of science are the laws, theories and principles that govern the behavior of nature, between them we have: The laws of thermodynamics, the special theory of relativity and the uncertainty principle